2015
DOI: 10.1186/s13065-015-0130-3
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical composition, antiparasitic and α–glucosidase inhibition activities from Pelliciera rhizophorae

Abstract: BackgroundPanama has an extensive mangrove area and it is one of the countries with the highest biodiversity in America. Mangroves are widely used in traditional medicine, nevertheless, there are very few studies that validates their medicinal properties in America. Given the urgent need for therapeutic options to treat several diseases of public health importance, mangrove ecosystem could be an interesting source of new bioactive molecules. This study was designed to evaluate the potential of Pelliciera rhizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 28 publications
4
17
0
Order By: Relevance
“…A. rotundifolia is a small tree originating from the Plumbaginaceae family with a height of 2–3 m. It has broad and ovate leaves, 5–8.8 cm long and 4.5–8.5 cm wide [44,45]. The species is mainly grown in Bangladesh and is used to cure inflammatory and painful arthritis [72,73].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A. rotundifolia is a small tree originating from the Plumbaginaceae family with a height of 2–3 m. It has broad and ovate leaves, 5–8.8 cm long and 4.5–8.5 cm wide [44,45]. The species is mainly grown in Bangladesh and is used to cure inflammatory and painful arthritis [72,73].…”
Section: Resultsmentioning
confidence: 99%
“…P. rhizophorae , also known as tea mangrove, is endemic to the coastline of Central America [44]. It comes from the Tetrameristaceae family.…”
Section: Resultsmentioning
confidence: 99%
“…Recent advances in drug discovery in Panama, specifically bioactive components extracted from the bacterium Bacillus pumilus , which was isolated from the black coral Antipathes sp., have shown the ability to constrain the growth of T. cruzi [ 73 ]. Other compounds derived from Panamanian isolates of the mangrove Pelliciera rhizophorae have also demonstrated selective anti-parasitic activity against T. cruzi [ 74 ]. It is worth mentioning that drug trials in Panama using bioactive components extracted from bacteria, corals, and other trypanostatics have all been in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrated the utility of the macro-ecological approach to better understand the spatial-temporal transmission dynamic of leishmaniasis in Panama [ 116 ], but similar work on CHD has not yet been conducted. In addition, there is a need for developing new and innovative strategies for vector control and more effective and less toxic drugs to treat infected people [ 72 , 74 ]. More specifically, scientific studies about population genetics and niche dynamics of major epidemiologic components of CHD (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…α-glucosidase enzyme bioassays were conducted following the protocol of Lopez et al (2015) using acarbose as a positive control.…”
Section: Malaria and α-Glucosidase Bioassaysmentioning
confidence: 99%